Improved ZIF-8 membrane: Effect of activation procedure and determination of diffusivities of light hydrocarbons - Pan, Yichang; Liu, Wei; Zhao, Yingjie; Wang, Chongqing; Lai, Zhiping (Journal of membrane science, 2015)
Zeolitic imidazolate framework ZIF-8 has shown great potential for effective separation of hydrocarbon mixtures based on its intrinsic ultramicroporous feature. In order to explore the permeation and diffusion properties of hydrocarbons through ZIF-8 membrane, high-quality ZIF-8 membranes with a separation factor of ~90 for propylene/propane are successfully prepared via optimizing the activation processes. Single-component permeation data for hydrocarbons (C1–C4) through the improved ZIF-8 membrane are measured and analyzed by Maxwell–Stefan (MS) model to get the transport diffusivities of these hydrocarbons. The diffusivity values of hydrocarbon compare well with those obtained by other experimental techniques. Binary mixture permeation also can be well predicted through single-component adsorption parameters. •The quality of ZIF-8 membranes was improved by optimizing the activation process.•The separation factor for propylene/propane mixtures was improved to ~90.•Permeation of hydrocarbons can be well described by Maxwell-Stefan model.•The transport diffusivities of hydrocarbons were obtained.